Ergonomics assessment of drudgery in rice-wheat production system in India: a case study of women farmers - Joshi, Pratibha; Mahra, Girijesh Singh; Jethi, Renu; Satyapriya; Singh, Rahul; Bishnoi, Sitaram; Sahu, Subhashree; Barua, Sukanya; Sarkar, Sujit; Burman, Rajarshi Roy (Frontiers in Sustainable Food Systems, 2024)
Farm women are forced to work in extremely hazardous conditions because they lack access to improved agricultural technologies, making agricultural work one of the physically demanding jobs that requires physiological endeavor and good posture. It is also very exhausting, time-consuming, and stressful. The study was designed to evaluate and quantify the drudgery involved in the ricewheat production system for rural women. Three replications of a ten-minute work cycle without a break were used to assess the physiological and postural demands of various farm tasks on the female workers. Observations were recorded on farm women worker with normal health, without any major illness, regularly involved in farm operations. In the attempt to obtain and analyze the prioritized drudgery experiences in crop production activities through drudgery assessment and reduction, various ergonomically sound farm tools and implements were provided for crop cultivation and intercultural operations. Data for indicating musculoskeletal disorders were analysed by ergonomics assessment of postural and biomechanical assessments using Human Physical Drudgery Index (HPDI) resulted in the maximum drudgery reflecting very high risk in transplanting (48.4 %), followed by threshing (47.2 %), load carrying (46.00 %) and harvesting (45.14 %). For physiological ergonomics quantifications these most drudgery prone activities in rice-wheat production system i.e. transplanting, harvesting, threshing &post-harvest, and load carrying were evaluated and it was found that drudgery is caused with different activities with reflects working energy expenditure rate ranges from ~7.00 to 12.00 (kJ/min) and Total Cardiac Cost of Wok (TCCW) ~ 331.00 to 524.00. Multivariate regression analysis was employed to drive relationships between energy expenditure rate (dependent variable)rate and other independent variables as age, Body Mass Index (BMI), Mid Upper Arm Circumference (MUAC), Calf circumference (CC), skinfold measurements, body density (D), % body fat, fat mass, fat free mass (kg). It was found that energy expenditure rate during various crop production practices is positively correlated with independent variables (R= 0.721, R 2 =0.520, Adjusted R 2 =0.518, Standard Error of Estimate=0.0324, Durbin-Watson=1.531). It was found that with higher physiological parameters the corresponding energy expenditure is maximizing relating to the drudgery in respective agricultural activities.